Ragam Komunikasi Dakwah bi Al-Lisan dalam Perspektif Al-Qur’an - Abdul Rohman; Abdul Rahman; Amin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
This article aims to explore the various forms of communication of da'wah bi al-Lisān in the Koran. This article is based on a literature review or library research, using qualitative methods. The analytical approach used is content analysis and is described using descriptive analysis methods. The research results show that there are five types of bi al-Lisān da'wah communication contained in the Al-Qur'an. The five types of da'wah communication are communicating with correct words (qaulan sadīdan), communicating with eloquent words (qaulan balīghan), communicating with noble words (qaulan karīman), communicating with easy words (qaulan maisūran) and communicating with good words. gentle (qaulan layyinan). All of these communication patterns can be implemented in everyday communication according to the context, conditions and interlocutor. This research is limited to studying various types of communication from an Al-Qur'an perspective, so future research needs to perfect this study by discussing effective communication in an educational environment from an Al-Qur'an perspective through more comprehensive methods and approaches.